Attenuation of everolimus-induced cytotoxicity by a protective autophagic pathway involving ERK activation in renal cell carcinoma cells - Zeng YZ; Tian XF; Wang Q; He WY; Fan J; Gou X (Dove Medical Press, 2018)
Yizhou Zeng, Xiaofang Tian, Quan Wang, Weiyang He, Jing Fan, Xin Gou Department of Urinary Surgery, The First Affiliated Hospital of Chongqing Medical University, Yuzhong District, Chongqing, China Aim: The mammalian target of rapamycin (mTOR) pathway is a critical target for cancer treatment and the mTOR inhibitor everolimus (RAD001) has been approved for treatment of renal cell carcinoma (RCC). However, the limited efficacy of RAD001 has led to the development of drug resistance. Autophagy is closely related to cell survival and death, which may be activated under RAD001 stimulation. The aim of the present study was to identify the underlying mechanisms of RAD001 resistance in RCC cells through cytoprotective autophagy involving activation of the extracellular signal-regulated kinase (ERK) pathway. Methods and results: RAD001 strongly induced autophagy of RCC cells in a dose- and time-dependent manner, as confirmed by Western blot analysis. Importantly, suppression of autophagy by the pharmacological inhibitor chloroquine effectively enhanced RAD001-induced apoptotic cytotoxicity, as demonstrated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and Western blot analysis, indicating a cytoprotective role for RAD001-induced autophagy. In addition, as was shown by the MTT assay, flow cytometry, and Western blot analysis, RAD001 robustly activated ERK, but not c-Jun N-terminal kinase and p38. Activation of ERK was inhibited by the pharmacological inhibitor selumetinib (AZD6244), which effectively promoted RAD001-induced cell death. Moreover, employing AZD6244 markedly attenuated RAD001-induced autophagy and enhanced RAD001-induced apoptosis, which play a central role in RAD001-induced cell death. Furthermore, RAD001-induced autophagy is regulated by ERK-mediated phosphorylation of Beclin-1 and B-cell lymphoma 2, as confirmed by Western blot analysis. Conclusion: These results suggest that RAD001-induced autophagy involves activation of the ERK, which may impair cytotoxicity of RAD001 in RCC cells. Thus, inhibition of the activation of ERK pathway-mediated autophagy may be useful to overcome chemoresistance to RAD001. Keywords: apoptosis, autophagy, everolimus, ERK, renal cancer, selumetinib